Problems which Confront Renal Transplant Recipients - Jaddoue, Batool; AL-Mallah, Suhban (Iraqi National Journal of Nursing Specialties, 2008)
Objective: The study objectives are to identify the problems which confront renal transplant recipients( RTRS).Methodology: A descriptive study was carried out at two Teaching Hospitals with kidney transplantcenters. Surgical specialties and Al-Karama outpatients,clinics for ( RTRS) ,and three TeachingHospitals; Medical city, Al-Karama and Al-Yermok which were responsible for immunosuppressivedrugs distribution .Starting from October ,1st 2006 to the end of July 2007.To achieve the objectivesof study, a non-probability (purposive) sample of 150 ( RTRS) who were attending to the outpatientclinic of the above listed hospital were selected according to the criteria of the study sample .The finalized questionnaire contained (83) items. The content validity of the instrument wasestablished through penal of (14) experts.Reliability of the problems scales was determined by test-retest method which was estimated asaverage (r=0.76).Data was gathered by interview technique using the questionnaire format and data was analyzed byapplication of descriptive and inferential statistical methods.Results: The results of the study indicated that the ( RTRS) confront (83 ) problems and affected bythese problems with different severity level, high, moderate, and low.Recommendation: According to the results of this study, the researcher recommended that theprovision of the necessary post transplant medicines from easy to reach centers.